Zatoichi in Desperation Based on a Short Story by Kan Shimozawa - Katsu, Shintaro; Morita, Fujio; Taichi, Kiwako; Yoshizawa, Kyoko (Zatoichi: The Blind Swordsman Collection, 2019)
Star Shintaro Katsu sits in the director's chair for this psychedelic and unremittingly bleak entry in the Zatoichi series, which is unlike any other in its grind-house grimness. A tale of innocence corrupted by sadistic, sleazy criminality, the film is propelled by Easy Rider–esque editing and a trippy seventies funk score by Kunihiko Murai. [www.criterion.com]